2021
DOI: 10.25122/jml-2021-0155
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve gastrectomy versus mini-gastric bypass and their effects on type II diabetes mellitus and weight loss outcome

Abstract: Bariatric surgeries such as sleeve gastrectomy; mini-gastric bypass surgery are successful weight reduction surgeries which significantly impact metabolic syndrome. The purpose of this research was to assess the impact of laparoscopy gastrectomy and mini-gastric bypasses on weight decrease and diabetes remission of diabetic mellitus type 2 through two years of monitoring. Furthermore, this study looked at the difference between the two procedures regarding their efficacy and identify which one is proper for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Other previous studies, such as those of Wang et al [33], Magouliotis [34], Akool et al [35], and Quan et al [36], also emphasized the better OAGB effect on DM. In a recent meta-analysis study by Ding et al [37], where four RCTs including more than 200 patients were analyzed, OAGB showed a distinctively higher DM remission rate than SG, with a signi cant reduction in HbA1c levels despite comparable EBMIL% at the short-term follow-up.…”
Section: Discussionmentioning
confidence: 75%
“…Other previous studies, such as those of Wang et al [33], Magouliotis [34], Akool et al [35], and Quan et al [36], also emphasized the better OAGB effect on DM. In a recent meta-analysis study by Ding et al [37], where four RCTs including more than 200 patients were analyzed, OAGB showed a distinctively higher DM remission rate than SG, with a signi cant reduction in HbA1c levels despite comparable EBMIL% at the short-term follow-up.…”
Section: Discussionmentioning
confidence: 75%
“…The resolution of hypertension with MGB is 87.5%(Musella et al, 2014).Laparoscopic mini gastric bypass is effective, safe, and reversible procedure and is associated with minor complications, mortality rates, and high excess weight loss. MGB is an excellent alternative to RYGB for treating diabetic obese patients(Akool et al, 2021). The OAGB/MGB technique simplifies bariatric surgery with lower complications and mortality.…”
mentioning
confidence: 99%